Effect of alkaline and benzoyl chloride treatments on the mechanical and morphological properties of sugar palm fiber-reinforced poly(lactic acid) composites - Faisal Khan, Sherwani Shah; Salit, Mohd Sapuan; Leman, Zulkiflle; Zainudin, Edi Syams; Abdan, Khalina (SAGE Publications, 2021)
The present study deals with the effects of alkaline and benzoyl chloride treatments of sugar palm fibers (SPFs) on the mechanical and morphological properties of SPF-reinforced poly(lactic acid) (PLA) composites. Seven different parameters of SPFs were compared, which were untreated, three alkaline solution concentrations of 4%, 5%, and 6% for alkaline treatment, and 50 ml benzoyl chloride-treated SPFs at three different soaking durations of 10, 15, and 20 min. Composites of 30 wt.% SPF–reinforced 70 wt.% PLA were prepared by using a Brabender plastograph mixer and a hot press. The tensile, flexural, and impact properties of the SPF/PLA composites were improved after alkaline and benzoyl chloride treatments on the SPFs. However, the best tensile, flexural, and impact properties of the composites were observed at 6% alkaline treatment of SPF; the morphological analysis also supported this. The 6% alkaline treatment of the SPF/PLA composite demonstrated the highest tensile, flexural, and impact strength values of 17.08 MPa, 32.34 MPa, and 4.39 kJ/m2, respectively. These treated SPF/PLA composites could be appropriate for automobile component applications.